Automatyka, sterowanie, zarządzanie : książka jubileuszowa z okazji 70-lecia urodzin profesora Kazimierza Mańczaka * Problemy zarządzania ryzykiem - Kulikowski, Roman (1928–2017) (Instytut Badań Systemowych. Polska Akademia Nauk, 2002)
The risk management problems are formulated using the concept of two-factors utility Junction, introduced. Using that concept in the present paper one is concerned with the decisions support related to capital allocation in the two generał risky spheres (portfolios) of activity: profits (investment, innovations) and expenses ( risk prevention, insurance etc). The utilities, appropriate for the se spheres, can be derived using simple (two-scenarios) forecasting model. Then the optimum decisions, concerned with capital allocation among the projects in each portfolio can be explicity derived.
[1-2], 167-181 stron ; 21 cm
Bibliografia s. 180-181